Pawnshop Marketing by Empowering Decisions through Equity and Promotion: Pemasaran Pegadaian dengan Memberdayakan Keputusan melalui Kesetaraan dan Promosi - Detak Prapanca; Salsabilla, Kania Savi (Indonesian Journal of Law and Economics Review, 2024)
This study investigates the impact of literacy empowerment, brand equity, and promotion on customer decisions regarding pawnshop products in Sidoarjo, Indonesia. Through a quantitative approach involving 96 respondents and regression analysis, the study reveals significant positive effects of these factors on customer decisions. Findings highlight the importance of enhancing literacy empowerment and promotional efforts in the pawnshop industry, while leveraging brand equity to bolster customer engagement. These insights offer valuable guidance for refining marketing strategies and fostering customer loyalty among pawnshop companies in Sidoarjo, suggesting avenues for future research to explore additional variables and expand sample sizes for a more comprehensive understanding of customer behavior in this context. Highlighgt: Quantitative analysis: Regression with 96 respondents for pawnshop customer decisions. Marketing strategy: Enhance literacy, promotion, leverage brand equity for customer engagement. Future research: Explore variables, expand samples for Sidoarjo's pawnshop industry understanding. Keyword: Pawnshop industry, Customer decisions, Literacy empowerment, Brand equity, Promotion.